2009
DOI: 10.1007/s10646-009-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Compromised immune competence in free-living tree swallows exposed to mercury

Abstract: Mercury is a pervasive environmental contaminant and a well-documented immunosuppressor. However, little is known about the effects of mercury contamination on health of free-living vertebrate populations. The South River in Virginia, USA was heavily contaminated with industrial mercury from 1929 to 1950, and recent studies have documented high levels of circulating mercury in riparian songbirds breeding below the site of contamination. Here we used two standardized immune assays, mitogen-induced swelling in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 23 publications
0
61
2
Order By: Relevance
“…Despite the fact that individuals collected from the contaminated site had very high tissue concentrations of Hg (female: 5.66±0.48mgkg ; neonate: 0.20±0.11mgkg 1 drymass), we detected no effects of Hg on healing ability of female N. sipedon or their offspring. This is contrary to previous studies that have shown that Hg affects vertebrate immune function (Spalding et al, 2000;Finkelstein et al, 2007;Hawley et al, 2009). However, two recent studies found few adverse sublethal effects of maternally transferred Hg in neonatal N. sipedon (Chin et al, 2013a;Chin et al, 2013b), suggesting that our study species may be more tolerant of Hg than many other species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that individuals collected from the contaminated site had very high tissue concentrations of Hg (female: 5.66±0.48mgkg ; neonate: 0.20±0.11mgkg 1 drymass), we detected no effects of Hg on healing ability of female N. sipedon or their offspring. This is contrary to previous studies that have shown that Hg affects vertebrate immune function (Spalding et al, 2000;Finkelstein et al, 2007;Hawley et al, 2009). However, two recent studies found few adverse sublethal effects of maternally transferred Hg in neonatal N. sipedon (Chin et al, 2013a;Chin et al, 2013b), suggesting that our study species may be more tolerant of Hg than many other species.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, many immunosuppressive contaminants can be maternally transferred from a female to her offspring during sensitive stages of development (Eisenreich et al, 2009;Bergeron et al, 2010). Exposure to contaminants could provide a source of variation in female and offspring immunocompetence, resulting in adverse effects such as reduced antibody responses and impaired T-cell function (Hawley et al, 2009;Pölkki et al, 2012). Because both parental and environmental sources can have multi-generational effects on phenotype, it is important to understand the contribution that each of these factors has on immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also quantified the response of nestlings to PHA (Sigma-Aldrich) by injecting the patagium (wing web) of nestlings with 0.15 mg of PHA dissolved in 30 μl phosphate-buffered saline (after Smits et al, 1999;Hawley et al, 2009). The injection of PHA leads to localized swelling due to the influx and proliferation of leukocytes and T-cells at the injection site (Martin et al, 2006) and a build-up of free radicals that are produced during phagocytosis by leukocytes (Peretz, 1989).…”
Section: Immune Responsementioning
confidence: 99%
“…Although less is known about the effects of mercury in avian invertivores, dosing studies indicate that this foraging guild is at greater risk of exposure than avian piscivores (Heinz et al 2009). Reduced reproductive success and suppressed immune function has been related to mercury exposure in the Tree Swallow (Tachycineta bicolor), an invertivore songbird (Brasso and Cristol 2008, Hawley et al 2009, Hallinger and Cristol 2011. Additionally, one of the more insightful field-based studies on an avian invertivore was conducted on the Carolina Wren (Thryothorus ludovicianus) at 2 contaminated river floodplains in Virginia, where adult reproductive impairment was quantified with known mercury body burdens (Jackson et al 2011a).…”
Section: Introductionmentioning
confidence: 99%